Press Information on Activities of Ministers of Education of Bulgaria, Sweden and Hungary Visiting Poland in 1935 - Gołdyn, Piotr (Biuletyn Historii Wychowania, 2018)
The renascent Polish state was being built in the interwar period (1918–1939), developing its position on all possible levels in the international arena. One of these was education and culture. Poland signed a lot of international agreements in this field. This was connected with visits by our ministerial representatives to other countries and with arranging visits in Poland for guests from different countries. In 1935, three ministers of education from abroad visited Poland: Todor Radev (Bulgaria), Artur Engberg (Sweden) and Bálaint Hóman (Hungary). The purpose of the visit of the first two ministers was the signing of the Polish-Bulgarian and Polish-Swedish cultural agreements. The Hungarian minister of education came to Poland to assess the implementation of the agreement which had been signed between Poland and Hungary a year before. While staying in Poland, beside official meetings with the President and the Ministers of education and foreign affairs, our guests visited various educational institutions in cities such as Warsaw, Krakow, Poznań or Vilnius. The press took a lively interest in those visits, reporting them on an ongoing basis. Apart from news reports, also editorials and even articles were published. These were devoted to some of the educational and cultural issues of our guests’ countries.